Pemanfaatan Limbah Batang Singkong dan Serat Tandan Kosong Kelapa Sawit (TKKS) sebagai Bahan Dasar Pot Organik - W, Nazova Falhbian; Oktafri, Oktafri; Asmara, Sandi; Kuncoro, Sapto (Jurnal Agricultural Biosystem Engineering, 2022)
Before planting, generally the seed is sowed in polybag that made of plastic (on organic).  For excessive use of polybag it can damage the environmental.  To prevent more severe environmental damage, it is necessary to find a safe way for the sustainability of environmental quality, that is by using organic materials. There are many organic materials can be used for seedling pots.  Two of them are cassava stem waste and Oil Palm Empty Fruit Bunches (OPEFB). OPEFB can increase strength and stiffness of wall of the pots (organic seedling pots).  To glue cassava stem waste and OPEFB then add enough adhesive material.  This research was held in October to December 2019 at Laboratory of Power and Agricultural Machinery and Laboratory of Land and Water Resources Engineering, Department of Agriculture Engineering, Faculty of Agriculture, University of Lampung.  The method of this research is Completely Randomized Design, with composition of ingredients cassava stem and OPEFB that consist 6 levels; P1 is 70% cassava stem and 30% OPEFB, P2 is 60% cassava stem and 40% OPEFB, P3 is 50% cassava stem and 50% OPEFB, P4 is 40% cassava stem and 60% OPEFB, and P5 is 30% cassava stem and 70% OPEFB. The result of this research showed that characteristic of test about moisture, density, impact resistance index, and water absorption had significant on combination of mixed materials.  For crops test with green lettuce, the result showed that height of crop, number of leaves, and root length were not significant on combination of mixed materials.  The best result of organic seedling pots in this research is on treatments of P3; 50% cassava stem and 50% OPEFB, with moisture is 11,46%, density is 0,28 g/cm3, impact resistance index is 98,04%, and water absorption capacity is 128,2 %.  Keywords:  Cassava Stem Waste, Characteristic Test, Crops Test, OPEFB waste, and Organic Seedling Pots.